Dynamic Response Analysis of Trapezoidal Basins on Numerical Models - Ozaslan, Bilal; Hasal, M. Emre; Khanbabazadeh, Hadi; Akbas, Merve; Iyisan, Recep (Iop Publishing Ltd, 2020)
The severity and spatial distribution of ground motion are affected by geological and geotechnical conditions as well as earthquake source properties. The characteristics of ground motion at a particular site depend on many factors such as tectonics of the region, rupture mechanism, source distance, geological formations and local soil conditions and subsurface topography. Thus, the estimation of surface ground motion during earthquakes is a challenging issue in civil engineering. Consequently, the research investigates an answer to the question of how the surface movement would change as a result of combinations of basic wave phenomena in alluvial basins with soil nonlinearity where basin width is comparable to depth. In this study, one and two-dimensional dynamic analyses were performed under different levels of bedrock motion excitation by using idealized symmetrical basin models to research the effects of geotechnical site conditions and bedrock inclination of basin edge for soft site class defined by seismic codes. Geotechnical properties of the soft soil layers in the models were defined as site class E that mostly needed site specific dynamic analysis by classification of NEHRP 2015 provisions. The top layers of basin models are soft cohesive alluvium underlain by stiffer material. In the basin models, the soil layers were assumed to extend horizontally and limited with basin edges having a constant slope. The acceleration time histories and response spectrums were calculated at surface points with equal interval on the top of the basin performing one and two-dimensional dynamic analyses by excitation of 22 strong ground motions. The response spectrum values and amplifications calculated for different sections of the basin from the two and one dimensional (2D and 1D) dynamic analyses. Consequently, the impact factors of the basin effect could be derived depending on location and periods as Sae(T)(2D)/Sae(T)(1D).
5th World Multidisciplinary Civil Engineering-Architecture-Urban Planning Symposium (WMCAUS) -- JUN 15-19, 2020 -- Prague, CZECH REPUBLIC
Keywords: Amplification; Motion